Metformin Use Is Not Associated With B12 Deficiency or Neuropathy in Patients With Type 2 Diabetes Mellitus in Qatar - Elhadd, Tarik; Ponirakis, Georgios; Dabbous, Zeinab; Siddique, Mashhood; Chinnaiyan, Subitha; Malik, Rayaz A. (Frontiers in Endocrinology, 2018)
Background: Metformin may lead to B12 deficiency and neuropathy. There are no published data on the prevalence of Metformin related B12 deficiency and neuropathy in the Arabian Gulf. Aims: Determine whether Metformin intake is associated with B12 deficiency and whether B12 deficiency is associated with diabetic peripheral neuropathy (DPN) and painful diabetic neuropathy. Methods: Patients with Type 2 Diabetes Mellitus (T2DM) (n=362) attending outpatient clinics at HMC underwent assessment of B12 levels, the DN4 questionnaire, and vibration perception threshold (VPT). Results: Comparing Metformin to non-Metformin users there were no differences in B12 levels, VPT or DN4. The prevalence of B12 deficiency (B12 < 133 pmol/l) was lower (P<0.01) in Metformin (8%) compared to non-Metformin (19%) users. Patients with B12 deficiency had a comparable prevalence and severity of sensory neuropathy and painful neuropathy to patients without B12 deficiency. Conclusion: Serum B12 levels were comparable between Metformin and non-Metformin users with T2DM in Qatar. T2DM patients on Metformin had a lower prevalence of B12 deficiency. Furthermore, the prevalence and severity of neuropathy and painful diabetic neuropathy were comparable between patients with and without B12 deficiency.